THE EFFECT OF ONLINE-BASED TRAINING AND ORGANIZATIONAL SUPPORT ON COMPETENCY DEVELOPMENT OF STATE CIVIL APPARATUS (ASN) AT THE REGIONAL REVENUE AGENCY OF RIAU ISLANDS PROVINCE - Novita Selfrida Simangunsong; Tibrani; Hanafi Siregar; Zulkifli; Dhenny Asmarazisa (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study examines the effect of online-based training and organizational support on the competency development of State Civil Apparatus (ASN) at the Regional Revenue Agency (Badan Pendapatan Daerah) of Riau Islands Province. The rapid digital transformation in Indonesian public administration necessitates empirical evidence on how e-learning modalities and institutional support mechanisms contribute to building civil servant competencies. Employing a quantitative research design with a cross-sectional survey approach, this study collected primary data from 86 ASN respondents using proportional stratified random sampling. Data were analyzed using multiple linear regression through SPSS version 26. The findings reveal that online-based training (X₁) has a positive and significant effect on competency development (Y) with a regression coefficient of β = 0.412 (t = 4.237, p < 0.01), and organizational support (X₂) also demonstrates a positive and significant effect with β = 0.389 (t = 3.985, p < 0.01). Simultaneously, both variables significantly influence competency development (F = 38.741, p < 0.01) with an adjusted R² of 0.478, explaining 47.8% of the variance. These results confirm that strategic investment in digital learning platforms combined with robust organizational support systems is essential for enhancing ASN competencies in regional government agencies. The study contributes to public administration literature by providing empirical evidence from an archipelagic province context, offering practical implications for human resource development policy in Indonesian local governments.